Dipyridinium 2,2'-dithiodinicotinate - Ariffin, Azhar; Ng, S.W.; Yehye, W.A.; Rahman, N.A. (International Union of Crystallography, 2009)
The dianion of the title salt, 2C(5)H(6)N(+) center dot C(12)H(6)N(2)O(4)S(2)(2-), lies on a special position of 2 site symmetry that relates one thionicotinate part to the other, and the dihedral angle between the niotinate planes is 89.2 (2)degrees. The pyridinium cations are hydrogen bonded to the carboxylate group by way of N-H center dot center dot center dot O links.